(untitled) (European Journal of Formal Sciences and Engineering, 2021)
Simulated laboratories are an effective tool to complement teaching and learning processes, in this case, in the area of nuclear physics and related sciences. They can be used in universities, schools, and research centers for personnel ramp up and training. This work presents the development of a simulator of a nuclear radiation counter and the elements used in experiments alongside it, such as simulated radioactive sources, absorbing materials and dispersing materials of radiation. This simulator allows us to verify the scientific laws that are involved in the interaction of radiation with matter, in a safe and reproducible way. The simulated laboratory experiments include determining the plateau curve of a Geiger-Müller tube, beta particle absorption and backscattering, and radioactive background. The data obtained from the simulations is based on the real experiments, eliminating the inherent risks of the manipulation of radioactive materials. This also allows to verify theoretical concepts in practice, strengthening the learning process and incentivizing research, interpretation, integration and communication of the obtained results. By incorporating this simulator in the multidisciplinary teaching and learning processes in STEM fields, it is possible to run these laboratories in a simple manner using non-radioactive materials.